Estudo microestrutural e resistência à corrosão de uma liga de Au soldada a laser, empregada em prótese sobre implantes - Dos Santos, Márcio Luiz [UNESP] (2002)
In this work, welded Au alloy joints, used for prosthesis supported by implants, have been studied before and after to laser welding processes. A refined dendritic microstructure was observed in the welding area. The base metal exhibited a two-phase granular microstructure with larger hardness and the appearance of Au precipitate. The electrochemical experiments, in NaCl 0.15 mol.L-1 solution at room temperature, which are appropriate to simulate corrosion at oral environment conditions, showed that the joint has a better performance when compared to base metal; probably due to the metallurgical structure in the region.